2020
DOI: 10.3389/fmats.2020.00244
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of an Equiatomic CoCrFeMnNi High-Entropy Alloy- a Comparison Between Selective Laser Melting and Cast

Abstract: The corrosion behaviors of equiatomic CoCrFeMnNi high-entropy alloys (HEAs) were comparatively investigated between selective laser melting (SLM) and casting. The cast sample shows better corrosion resistance in 3.5 wt.% NaCl solution than the SLM printed sample due to the higher density of dislocations, pores, and cracks in SLM samples, which significantly reduces their corrosion resistance. Furthermore, it is found that the corrosion resistance is different between the planes parallel and perpendicular to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The equilibrium phases of Ni 3 Ti and Co 3 Ti were reported as η (D0 24 ) phase and γ 0 (L1 2 ) phase, respectively. [48][49][50] The equilibrium phase ratios in MPEA1 and MPEA2 were calculated using ThermoCalc software (TCNI6 database) (Figure 12). The calculated phase ratio of η-phase was lower in MPEA2 than in MPEA1 in all temperature ranges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The equilibrium phases of Ni 3 Ti and Co 3 Ti were reported as η (D0 24 ) phase and γ 0 (L1 2 ) phase, respectively. [48][49][50] The equilibrium phase ratios in MPEA1 and MPEA2 were calculated using ThermoCalc software (TCNI6 database) (Figure 12). The calculated phase ratio of η-phase was lower in MPEA2 than in MPEA1 in all temperature ranges.…”
Section: Discussionmentioning
confidence: 99%
“…[ 46,47 ] The dense dislocation network was also suggested as a cause of lower corrosion resistance in the CoCrFeMnNi HEAs. [ 48 ] In as‐built specimens, such inhomogeneous distributions of elements and dislocations may have accelerated corrosion. Weight loss during H 2 SO 4 immersion was significantly reduced after the ST process for all specimens, possibly due to the homogenization of the microcellular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from SPS, SLM is the most widely studied AM technique for HEAs . HEAs that were successfully fabricated by SLM include CoCrFeNiMn [153,154,169,[176][177][178][179][180][181][182][183][184][185]188,[202][203][204][205][206]209,212,214,215,217,220,221], AlCrFeNiV [193], AlCoCrFeNi [170,190], Al-CoCrCuFeNi [194], CoCrFeNi [98,155,186,187,189,208,213,222], CoCr 2.5 FeNi 2 TiW 0.5 [223],…”
Section: Additive Manufacturing Of Heasmentioning
confidence: 99%
“…They have also shown that the properties of HEAs could be altered by changing the input parameters for AM process. For example, CoCrFeNiMn was manufactured with SLM by multiple researchers [153,154,169,[176][177][178][179][180][181][182][183][184][185]188,[202][203][204][205][206]209,212,214,215,217,220,221] and many of them acquired different mechanical properties for CoCrFeNiMn by changing input parameters in AM processes (refer Tables 1-3).…”
Section: Additive Manufacturing Of Heasmentioning
confidence: 99%
“…How a given HEA reacts in a corrosion environment depends on its microstructure, alloying elements, and processing methods. In recent years, corrosion resistance of CoCrFeMnNi HEA was investigated for samples produced by conventional methods [30][31][32][33] , DED [34] and SLM [35][36][37][38] . Xu et al [38] compared the corrosion properties of SLMed and as-cast CoCrFeMnNi and found that the former exhibit better corrosion resistance due to homogeneity of components and grain refinements.…”
Section: Introductionmentioning
confidence: 99%